El estrés en los docentes de inglés en las instituciones educativas secundarias públicas y privadas del distrito de Iquitos 2023 - Lozano Vasquez, Diana Isabel (2024)
The objective of this research was to compare the stress levels of English teachers in public and private secondary schools in the district of Iquitos 2023. The type of research was comparative with field design, contemporary transectional and multivariate. The study included 79 teachers; sampling was not used since the entire population was approached. The tool used was a survey with an ED-6 scale. The results show that teachers have a low level of stress with a mean of 79.16 for private educational institutions and a mean of 75.833 for public ones. In the dimensions of stress due to anxiety, depression, maladaptive beliefs, pressures, demotivation and poor coping stress, There is a mean of 82.452 for private and 79.125 for public institutions with respect to the first dimension, for the second a mean of 87.774 for private and 83.774 for public institutions, 774 for private and 83.333 for public, for the third a mean of 86.903 for private and 83.979 for public, the fourth dimension has a mean of 71.387 for private and 70.646 for public and for the fifth dimension with a mean of 70.677 for private and 68.271 for public and the last dimension, poor coping stress, does show a mean of 83.645 for private and 75.667 for public. In conclusion, there are no significant differences between the stress levels of English teachers in public and private institutions in the district of Iquitos 2023 (p-value =0,064 > α= 0,05).